POROČILO Z MEDNARODNE ZNANSTVENE KONFERENCE MANJŠALNICE V SLOVANSKIH JEZIKIH: OBLIKA IN VLOGA - Zemljak Jontes, Melita; Ulčnik, Natalija (Slavia Centralis, 2020)
The authors report on the international scientific conference Diminutives in Slavic Languages: Form and Role, which took place from 25 to 29 May 2015, organized by the Department of Slavic Languages ​​and Literatures, the Department of Translation Studies and the Slavic Society Maribor.